A luta pela terra e contra a grilagem no assentamento Irmã Dorothy Stang, Anapu/PA - OLIVEIRA, Deise Cristina Lima de (2024)
This present work aims to analyze how the struggle and resistance for land were fundamental for the reversal of an area that was previously designated for rural business implementation, to an area of production, life, and peasant farming. Like many other areas located in the Transamazônica region, the areas that will be analyzed in this work are completely related to the context of colonization of the Amazon and the arrival of peasants from various parts of the country, especially the northeastern region of Brazil. Therefore, the conflict over land ownership analyzed presents contradictory elements as we will present a group of people who previously could not resist the pressure from farmers and land grabbers, from the repressive forces of the State, but who in Anapu were able to resist, in a group activity that strengthened them in the consolidation of their struggle, their possessions, and the right to access land. In this way, we seek to understand how the struggle for land is related to the transformation of land that was previously used for cattle and grass into land for peasant cultivation and production, going through various violations of human rights and threats to the physical integrity of the families who dared to occupy land to build a home in this area. Thus, this study aims to address the movement of occupation of two plots of land located in the municipality of Anapu/PA, which were designated for the implementation of a rural company in 1976, as well as the peasant struggle for the reversion of these plots to agrarian reform through the fight and resistance for land. The objective of this study is to identify the journey of the land, from the allocation of Plot 96 and 97 to large landholdings, to its allocation for agrarian reform, determined judicially. We ethnographically examine the struggle for land, focusing on the political movement of the peasants, transforming work on the land into a strategy to confront land grabbing in the region.